2009
DOI: 10.1111/j.1468-1331.2009.02568.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous versus intravenous immunoglobulin in multifocal motor neuropathy: a randomized, single‐blinded cross‐over trial

Abstract: In MMN, short-term subcutaneous infusion of immunoglobulin is feasible, safe and as effective as intravenous infusion. Subcutaneous administration is an alternative option that adds flexibility to the treatment schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 32 publications
10
122
0
6
Order By: Relevance
“…The abstracts and/or full texts of the 34 studies were retrieved, evaluated in detail and filtered according to the eligibility criteria. After this stage five studies were left for inclusion in the review [27][28][29][30][31]. A hand search of the references of relevant citations resulted in an additional study being included in the final review [32].…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The abstracts and/or full texts of the 34 studies were retrieved, evaluated in detail and filtered according to the eligibility criteria. After this stage five studies were left for inclusion in the review [27][28][29][30][31]. A hand search of the references of relevant citations resulted in an additional study being included in the final review [32].…”
Section: Search Resultsmentioning
confidence: 99%
“…The majority (4/6) of the studies concluded that patients had demonstrated a preference for SC drug administration [27][28][29][30] proportions ranged from 44%-91%. Only one study reported that patients preferred IV drug delivery [32] and another found no difference in patient preference for either method [31].…”
Section: Patient Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized, single-blinded, crossover study was conducted in 9 patients responsive to IVIG and assessed by the dynamometric strength of affected muscles and the SF-36 quality-oflife questionnaire [83]. IVIG and SCIG were equally effective, the mean change in muscle strength after SCIG being 3.6 % versus 4.3 % after IVIG.…”
Section: Subcutaneous Immunoglobulinmentioning
confidence: 99%
“…First case reports in CIDP and MMN suggest that scIg is effective [Lee et al 2008;Köller et al 2006]. The results of randomized trials with scIg are expected to be published next year [Harbo et al 2008].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%